The Audiological Profile and Rehabilitation of Patients with Incomplete Partition Type II and Large Vestibular Aqueducts - Beyza Demirtaş; Merve Özbal Batuk; Hilal Dinçer D’Alessandro; Gonca Sennaroğlu (Journal of International Advanced Otology)
BACKGROUND: Incomplete partition type II (IP-II) malformation is often accompanied by a large vestibular aqueduct (LVA). In IP anomalies, the patient’s auditory rehabilitation requirements are decided according to the presence of inner ear structures and the degree of hearing loss (HL). There has been limited research on auditory rehabilitation (AR) requirement selection in patients diagnosed with IP-II and LVA. This study investigated the typical characteristics of HL and AR choices in patients diagnosed with IP-II and LVA.